Identification of cuprotosis-mediated subtypes, the development of a prognosis model, and influence immune microenvironment in hepatocellular carcinoma - Xiao, Jingjing; Liu, Zhenhua; Wang, Jinlong; Zhang, Shuaimin; Zhang, Yi (Frontiers in Oncology, 2022)
Purpose: Cuprotosis is a newly discovered form of non-apoptotic regulated cell death and is characterized by copper-dependent and associated with mitochondrial respiration. However, the prognostic significance and function of cuprotosis-related genes (CRGs) in HCC are unknown. This study aims to develop Cuprotosis-related pattern prediction models for the prognosis of patients with hepatocellular carcinoma (HCC), exploring the functional underlying the CRGs to the tumour microenvironment (TME) features influence. Experimental design: This study obtained transcriptome profiling and the corresponding clinical information from the TCGA and GEO databases. Besides, the Cox regression model with LASSO was implemented to build a multi-gene signature, which was then validated in the validation cohorts through Kaplan-Meier, Cox, DCA and ROC analyses. Results:According to the LASSO analysis, we screened out a cuprotosis-related pattern 5-gene combination (including PBK; MMP1; GNAZ; GPC1 and AKR1D1). A nomogram was constructed for the presentation of the final model. The ROC curve assessed the model's predictive ability, which resulted in an area under the curve values ranging from 0.604 to 0.787. Meanwhile, the risk score divided the patients into two groups of high and low risk, and the survival rate of high-risk patients was significantly lower than that of low-risk patients (P<0.01). The risk score could be an independent prognostic factor in the multifactorial Cox regression analysis (P<0.01). Functional analysis revealed that immune status, mutational loads, and drug sensitivity differed between the two risk groups. Conclusions: In summary, we demonstrated that CRGs are a promising candidate biomarker for HCC early detection, owing to their strong performance in predicting HCC prognosis and therapy.